New paths of medical ethics - Čović, Ante (Array, 1997)
The author of this essay comments on the thematic block New Medical Ethics, which appeared in the journal Društvena istraživanja 23-24 (3-4/1996), and enters upon an extended discussion on the methodological and philosophical aspects of bioethics (also called biomedical ethics and new medical ethics). The essay represents an attempt to explain the origins of the new medical ethics that is arising out of the new medical situation due to scientific-technological progress. The author distinguishes between positive and negative aspects of bioethics and reconstructs (taking into account he suppositions of Peter Singer) the structure of biomedical methods. He defines bioethics - based on the claim that it is necessarily affiliated with philosophy - as a specific, relational and multiperspectival ethics. Such an approach is formulated as an alternative to deductivist conceptions which consider bioethics as a part of applied ethics, but also as an alternative to bioethical trends (casuistry, principles of biomedical ethics, etc.) that do not permit openess to ethical and philosophical theory.